Childhood smoking is an independent risk factor for obstructive airways disease in women. Issue 8 (28th July 2004) - Patel, B D; Luben, R N; Welch, A A; Bingham, S A; Khaw, K-T; Day, N E; Lomas, D A; Wareham, N J
Abstract : Objective: To assess whether starting to smoke in childhood increases the risk of obstructive airways disease (OAD) in adult life. Methods: A retrospective cohort analysis was undertaken of 12 504 current and ex-smokers in the EPIC-Norfolk cohort. The main exposure was starting to smoke during childhood (age <16 years). Three definitions of OAD were used: doctor diagnosed asthma, doctor diagnosed bronchitis/emphysema, and "any OAD" (doctor diagnosed asthma or bronchitis/emphysema, or taking medication used in the treatment of OAD). Results: Childhood smokers had significantly more pack years of exposure and poorer lung function than subjects who started to smoke in adulthood (⩾16 years). Compared with starting in adulthood, starting to smoke in childhood was associated with a greater risk of bronchitis/emphysema in female smokers (OR 1.79, 95% CI 1.25 to 2.56) and ex-smokers of both sexes (OR 1.29, 95% CI 1.07 to 1.55 in men and OR 1.40, 95% CI 1.05 to 1.85 in women), and of "any OAD" in female smokers (OR 1.72, 95% CI 1.24 to 2.38) and male and female ex-smokers (OR 1.20, 95% CI 1.03 to 1.40 in men and 1.34, 95% CI 1.07 to 1.57 in women). After adjustment for pack years, childhood smoking was associated with poorer lung function (FEV1 92.3% predicted in adult smokers and 89.5% in childhood smokers, p = 0.03) and a greater risk of bronchitis/emphysema (adjusted OR 1.55, 95% CI 1.08 to 2.24) and for "any OAD" (OR 1.54, 95% CI 1.10 to 2.13) in female smokers but not in male and female ex-smokers. Conclusion: Starting to smoke in childhood is associated with an increased risk of airways disease because of the extra pack years smoked. In women, childhood smoking is itself an independent risk factor for the development of airways disease.